Folic Acid Fortification Prevents Morphological and Behavioral Consequences of X-Ray Exposure During Neurulation - Craenen, Kai; Verslegers, Mieke; Callaerts-Vegh, Zsuzsanna; Craeghs, Livine; Buset, Jasmine; Govaerts, Kristof; Neefs, Mieke; Gsell, Willy; Baatout, Sarah; D'Hooge, Rudi; Himmelreich, Uwe; Moons, Lieve; et al. (Frontiers in Behavioral Neuroscience, 2021)
Previous studies suggested a causal link between prenatal exposure to ionizing radiation and birth defects such as microphthalmos and exencephaly. In mice, these defects arise primarily after high-dose X-irradiation during early neurulation. However, the impact of sublethal (low) X-ray doses during this early developmental time window on adult behavior and morphology of central nervous system structures is not known. In addition, the efficacy of folic acid (FA) in preventing radiation-induced birth defects and persistent radiation-induced anomalies has remained unexplored. To assess the efficacy of FA in preventing radiation-induced defects, pregnant C57BL6/J mice were X-irradiated at embryonic day (E)7.5 and were fed FA-fortified food. FA partially prevented radiation-induced (1.0 Gy) anophthalmos, exencephaly and gastroschisis at E18, and reduced the number of prenatal deaths, fetal weight loss and defects in the cervical vertebrae resulting from irradiation. Furthermore, FA food fortification counteracted radiation-induced impairments in vision and olfaction, which were evidenced after exposure to doses ≥ 0.1 Gy. These findings coincided with the observation of a reduction in thickness of the retinal ganglion cell and nerve fiber layer, and a decreased axial length of the eye following exposure to 0.5 Gy. Finally, MRI studies revealed a volumetric decrease of the hippocampus, striatum, thalamus, midbrain and pons following 0.5 Gy irradiation, which could be partially ameliorated after FA food fortification. Altogether, our study is the first to offer detailed insights into the long-term consequences of X-ray exposure during neurulation, and supports the use of FA as a radioprotectant and antiteratogen to counter the detrimental effects of X-ray exposure during this crucial period of gestation.